My little town eaudiobook - Keillor, Garrison (HighBridge Audio, 2011)
"It's been a quiet week in Lake Wobegon, my home town . . ." Lake Wobegon has been Garrison Keillor's fictional home town-and America's-for almost 40 years. Many of us have grown up with "the little town that time forgot and the decades cannot improve." The Chatterbox Cafe, the Sidetrack Tap, the Church of Our Lady of Perpetual Responsibility, the Bunsens and the Krebsbachs, the Lake Wobegon Whippets-these are places, people, and sports teams we know and love, thanks to Keillor's ability to weave a story and tell it live.Never before collected, these expertly crafted tales are full of gentle humor, genuine emotion, and (more often than not) surprising insights into family, relationships, community, faith, and hope.